Critical Rationalism, Metaphysics and Science
XXII, 266 p.
Keywords: I suppose Joseph Agassi's best and dearest self-description, his cher ished wish, is to practice what his 1988 book promises: The Gentle Art of Philosophical Polemics. But for me, and for so many who know him, our Agassi is tough-minded, not tender, not so gentle. True to his beloved critical thinking, he is ever the falsificationist, testing himself of course as much as everyone else. How, he asks himself, can he engage others in their own self-critical exploration? Irritate? Question their logic, their facts, their presuppositions, their rationales? Subvert their reasoning, uncover their motives? Help them to lose their balance, but always help them, make them do it to, and for, themselves. Out of their own mouths, and minds, and imagination. A unique teacher, in classroom and out; not for everyone. Agassi is not quite a tight textual Talmudist disputant, not quite the competitor in the marketplace of ideas offered for persuasive sale, not quite the clever cross-examining lawyer advocate, not quite a philosopher-scientist, not a sceptic more than necessary, not quite embat tled in the bloody world but not ever above the battle either . . . but a good deal of all of these, and steeped in intelligence and good will.